Correlations in Emerging Market Bonds : The Role of Local and Global Factors - Hamann, A. (IMF Working Papers; Working Paper, 2010)
This paper examines the comovement in emerging market bond returns and disentangles the influence of external and domestic factors. The conceptual framework, set in the context of asset allocation, allows us to describe the channels through which shocks originating in a particular emerging or mature market are transmitted across countries and markets. We show that using a simple measure of cross-country correlations together with the commonly used average correlation coefficient can be more informative during episodes of heightened market instability. Data for the period 1997-2008 are analyzed for evidence of true contagion and common external shocks.